VACCINATION SAFETY: MODERN DATA - V.К. Tatochenko (Педиатрическая фармакология)
Vaccination aided disease control over infection pathology among the children led to elimination of smallpox and poliomyelitis, drastic decrease of the tuberculous meningitis recurrences, tetanus, measles and other infection diseases and their complications. At the same time, Russia is still afraid to apply certain vaccines. The reasons for that are mainly subjective. This is the unjustified caution related to the fear that it may cause severe vaccine associated complications. The data in view of the lecture indicates the safety of the vaccinal prevention procedures and measures for the prevention of their complications.Key words: vaccinal prevention, vaccination complications, vaccination safety, children.